Natural and accidental torsion in one-storey structures on elastic foundation under non-vertically incident SH-waves. - Avilés, Javier (Earthquake engineering & structural dynamics.)
Factors α and β used in equivalent static analysis to account for natural and accidental torsion are evaluated with consideration of soil?structure interaction. The combined torsional effects of structural asymmetry and foundation rotation are examined with reference to a single monosymmetric structure placed on a rigid foundation that is embedded into an elastic half-space, under to the action of non-vertically incident SH waves. Dynamic and accidental eccentricities are developed such that when used together with the code-specified base shear, the resulting static displacement at the flexible edge of the building is identical to that computed from dynamic analysis. It is shown that these eccentricities do not have a unique definition because they depend on both the selection of the design base shear and the criterion used for separation of the torsional effects of foundation rotation from those of structural asymmetry. Selected numerical results are presented in terms of dimensionless parameters for their general application, using a set of appropriate earthquake motions for ensuring generality of conclusions. The practical significance of this information for code-designed buildings is elucidated.